Pengaruh Nilai Tukar, Harga dan Total Produksi terhadap Ekspor Crude Palm Oil (CPO) Sawit di Provinsi Jambi Periode 2013-2022 - Neldawaty, Rika; Suherman, Suherman; Devalia Putri, Maisyah (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
The aim of this research is to analyze the price of CPO, the amount of production and the value of CPO exports in Jambi Province. This type of research is a form of research that is descriptive and associative. This research explains the influence of the independent variables, namely CPO price data (X1) and production quantity (X2) on the dependent variable, namely export value (Y) in Jambi Province for the 2013-2022 period. This research method is oriented towards secondary data analysis, obtained from the Jambi Province Plantation Service, Jambi Province Central Statistics Agency (BPS) Website, Bank Indonesia Website, World Bank Website, literature, library studies and sources that are related to the research object. The analysis technique uses multiple linear regression. Partial research results show that the development of Jambi Province's CPO export value, rupiah exchange rate, CPO price and production quantities tend to fluctuate every year. The CPO price variable has a positive and significant effect on the value of CPO exports in Jambi Province, the exchange rate variable has a negative and insignificant effect on the value of CPO exports in Jambi Province, while the amount of production has a positive and significant effect on the value of CPO exports in Jambi Province. Together they have a significant effect on the CPO export value of Jambi Province, amounting to 87.5 percent.